Turkey's liberal' liberals - Borovali, Murat (Sage Publications Inc, 2017)
This article seeks to address the increasingly pertinent concern of how to form a satisfactory liberal stance in the face of certain democratically mandated policies of non-liberal and even sometimes illiberal governments. To that end, a close analysis is provided of a particular debate that generated controversy in certain liberal circles in Turkey during the run-up to the referendum on constitutional amendments in 2010. Identifying and evaluating 5 factors which seemed to have influenced the opposing positions in the debate, the article tries to demonstrate how disagreement over the correct' liberal position entails differences in overall judgement of the political situation and assessment of the circumstances.
Keywords: Ak Party; İlliberal Democracy; Liberalism; Referendum; Turkey